-12m+8=-13m

Simple and best practice solution for -12m+8=-13m equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -12m+8=-13m equation:


Simplifying
-12m + 8 = -13m

Reorder the terms:
8 + -12m = -13m

Solving
8 + -12m = -13m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '13m' to each side of the equation.
8 + -12m + 13m = -13m + 13m

Combine like terms: -12m + 13m = 1m
8 + 1m = -13m + 13m

Combine like terms: -13m + 13m = 0
8 + 1m = 0

Add '-8' to each side of the equation.
8 + -8 + 1m = 0 + -8

Combine like terms: 8 + -8 = 0
0 + 1m = 0 + -8
1m = 0 + -8

Combine like terms: 0 + -8 = -8
1m = -8

Divide each side by '1'.
m = -8

Simplifying
m = -8

See similar equations:

| 19=7m+5(3-m) | | 2x-45=6 | | w^2=x+v^2 | | 7(6x+2)= | | x^2-45=20 | | (6c-5)+8(3c+4)= | | 12(3x+6)= | | -2(-2)(-3)(-4)-5= | | 6g=24-2(3+3g) | | 313+n=400 | | 5(h-2)-(3-2h)= | | 7=8x-5y | | 2(4x+9)= | | 2x+11=52-3x | | 4f*2+3f*(-2)= | | -13x+1=-90 | | 7x-7y=-5 | | -2(11b-3)= | | 5(9x+5)= | | -83=15x+7 | | 8x+2=91 | | 80=-8x+8 | | -8=-17x+26 | | 15a=10 | | 14x/2= | | 5c+34=-2(1-7c) | | x-7=2(4x-3) | | i-(-3)=9 | | 2x-y+x-2y=180 | | (2+i)-(4-6i)(-3+3i)= | | -13x+20=-123 | | X+6.3=-8.7 |

Equations solver categories